Prognostic value of CA125 in diffuse large B-cell lymphoma - Zhang, Jie; Jiang, Yijing; Chen, Long; Xu, Linyan; Ge, Bojian; Miao, Xiaobing; Xu, Xiaohong (Frontiers in Oncology, 2025)
BackgroundCarbohydrate antigen 125 (CA125) is one of the most commonly used tumor biomarker for evaluating the prognosis of solid neoplasms. It has been reported that serum CA125 is correlated with the prognosis of non-Hodgkin’s lymphoma. The objective of this study is to explore the clinical value of CA125 in diffuse large B-cell lymphoma (DLBCL).MethodsWe retrospectively analyzed the clinical and pathological data in a cohort of 315 newly diagnosed patients with DLBCL. In our case, the correlations between serum CA125 and clinicopathological parameters were analyzed. Kaplan-Meier survival curve and cox proportional hazards model were applied to evaluate the prognosis. The expression of CA125 in DLBCL paraffin tissues was detected by immunohistochemistry.Results82 patients (26%) with DLBCL had elevated serum CA125 levels at diagnosis. Elevated serum CA125 levels were associated with poor performances status, greater than or equal to 2 Extra-nodal sites, advanced Ann Arbor stage (III-IV), presence of B symptoms, presence of bulky mass, presence of effusion, intermediate/high-risk International Prognostic Index (IPI), elevated lactate dehydrogenase levels and reduced albumin levels. Patients with elevated serum CA125 levels at diagnosis had shorter progression free survival (PFS) and overall survival (OS). Multivariate analysis revealed that serum CA125, cell of origin, IPI score and albumin were independent prognostic factors for OS and PFS. In addition, the results of the immunohistochemistry indicated that none of the 82 DLBCL paraffin tissues expressed CA125 in lymphoma cells and the surrounding microenvironment cells.ConclusionsSerum CA125 detected at the initial diagnosis is a strong predictor of prognosis in patients with DLBCL.